The impact of dietary acid load on kidney function in individuals with chronic kidney disease: A literature review - Faza Yasira Rusdi; Harnavi Harun (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Chronic Kidney Disease (CKD) has been increasingly associated with dietary patterns, particularly a high Dietary Acid Load (DAL). Diets rich in animal protein and low in fruits and vegetables may contribute to metabolic disturbances that negatively affect the kidney function. This literature review aimed to evaluate the relationship between DAL and kidney function in individuals with CKD. A literature search was conducted using PubMed, ScienceDirect, and Google Scholar for studies published between January and June 2025. A total of 19,040 articles were included. After screening and eligibility assessment using the PRISMA approach, six studies were included. Review articles, clinical trials, and animal studies were excluded from the study. Data were analyzed descriptively to identify the association between DAL and renal outcomes in patients with CKD. The findings consistently indicated that a high DAL was associated with impaired kidney function, including lower serum bicarbonate levels, reduced glomerular filtration rate (GFR), and increased serum creatinine concentrations. Variations in study outcomes were observed due to differences in DAL assessment methods, such as dietary intake analysis and urinary net endogenous acid production (NEAP) measurement. In conclusion, a High DAL may contribute to CKD progression. Further longitudinal and interventional studies are required to clarify the causal effects of DAL reduction on renal health.